Complex Stability and an Irrevertible Transition Reverted by Peptide and Fibroblasts in a Dynamic Model of Innate Immunity - Abudukelimu, Abulikemu; Barberis, Matteo; Redegeld, Frank; Sahin, Nilgun; Sharma, Raju P.; Westerhoff, Hans V. (Frontiers in Immunology, 2020)
We here apply control analysis and various types of stability analysis to an in silico model of innate immunity that addresses the management of inflammation by a therapeutic peptide. Motivation is the observation, both in silico and in experiments, that this therapy is not robust. Our modelling results demonstrate how (i) the biological phenomena of acute and chronic modes of inflammation may reflect an inherently complex bi-stability with an irrevertible flip between the two modes, (ii) the chronic mode of the model has stable, sometimes unique, steady states, whilst its acute-mode steady states are stable but not unique, (iii) as witnessed by TNF levels, acute inflammation is controlled by multiple processes whereas its chronic-mode inflammation is only controlled by TNF synthesis and washout, (iv) only when the antigen load is close to the acute mode’s flipping point, many processes impact very strongly on cells and cytokines, (v) there is no antigen exposure level below which reduction of the antigen load alone initiates a flip back to the acute mode, (vi) adding healthy fibroblasts makes the transition from acute to chronic inflammation revertible, although (viii) there is a window of antigen load where such a therapy cannot be effective. This suggests that triple therapies may be essential to overcome chronic inflammation. These may comprise (i) anti Immunoglobulin-Light-Chain peptides, (ii) a temporarily reduced antigen load, and (iiia) fibroblast-repopulation or (iiib) stem-cell strategies.